Passive Cooling Solutions for High Power Server CPUs with Pulsating Heat Pipe Technology: Review - Li, Chenxi; Li, Ji (Frontiers in Energy Research, 2021)
Data centers are becoming more powerful and more integrated with the continuous development of smart cities, which brings us more technological convenience, but also generates a large amount of waste heat. At present, the efficient and green cooling scheme is one of the key researches and development points to ensure the stable and safe operation of power electronic devices and achieve energy saving and consumption reduction. As a branch of the heat pipe, the pulsating heat pipe is one of most promising passive cooling techniques among many candidates for its unique advantages such as small size, simple and compact structure, and high heat dissipation efficiency, but its application in data centers just begins, and there are few reports on research and implementation. Based on the introduction of the basic structure, working mechanism and outstanding advantages of pulsating heat pipes, this paper reviews in detail the researches on the factors affecting its performance, so as to evaluate the possibility of using pulsating heat pipes in data centers. Finally, the latest application and development of pulsating heat pipes applied to heat dissipation of high-power CPUs are summarized, which can provide a guidance for subsequent research and engineering application.